REGULATORY ISSUES AND CHALLENGES: GLOBAL NORMS AND RELIGIOUS CONSTRAINTS - Syahraini, Syahraini; Simahatie, Mai; Abdul Majid, Shabri; Handayani, Rita; Marliyah, Marliyah (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2022)
Regulation is a balancing act. Different, often contradictory, goals – flexibility and consistency, freedom and strict controls, innovation and crisis-avoidance, consolidation and conflicts of interest, efficiency and consumer protection, openness and protection of national firms – must be applied in proper dosages by people familiar with the political and cultural environment. The audit systems and incentive structures must be flexible yet strict enough to allow innovation but prevent rogue operations. Before the disruptions of the 1970s, regulators performed a mostly technical task outside of the political limelight. In recent years however, virtually every country – including those with well-established regulatory authorities and traditions – has been rocked by banking crises. By October 1998, regulators worldwide were committed to the implementation of the 'Core Principles for Effective Banking Supervision' issued in 1997 by the Basle Committee. Similarly, as of March 1999, the 102 signatories of the December 1997 Free Trade in Financial Services Agreement (under the aegis of the World Trade Organization) were expected to liberalize their markets which is directed at literature research. In this case, The author takes two problems based on the description on the background problem. The formulation of the problem is How the Value of Islam in Islam The Era of Globalization and How Globalization Affects Religious Values Islam. The research methods include: the type of research Library Research is research through literature review or literature. The data sources in this study are primary data, namely books that directly discuss on the Effect of Globalization on Islamic Religious Values. Data analysis techniques used to get the conclusion is descriptive qualitative by drawing conclusions deductively, namely how to draw conclusions from the general to the specific. The author draws conclusions and suggestions that: the influence of globalization covers many aspects of life. However, that doesn't t mean we cannot provide an understanding of globalization that includes all symptoms the. Looking at the aspects of globalization above, we can conclude that globalization is nothing but the application of rational and scientific knowledge to all activities in all areas of life or to all aspects Public.